Urgent plzzz..

Asked by 2806rahul | 16th Feb, 2010, 10:13: PM

Expert Answer:

For x = 3

P(3) = 2(3)3 - (3)2 - 13x3 - 6 = 54 - 9 - 39 - 6 = 0

(x-3) is a root.

Dividing P(x) by (x-3) we obtain, 2x2+5x+2

and the roots of the quadratic equation are,

x = {-5±(25-16)}/4 = -1/2 or -2.

Hence the factors are (x-3)(x+1/2)(x+2)

Regards,

Team,

TopperLearning.

 

Answered by  | 17th Feb, 2010, 06:07: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.